2007
DOI: 10.1210/en.2007-0864
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Induces Superoxide Generation via Rac1 Activation in Endothelial Cells

Abstract: Currently, aldosterone is believed to be involved in the development of cardiovascular injury as a potential cardiovascular risk hormone. However, its exact cellular mechanisms remain obscure. This study was undertaken to examine the effect of aldosterone on superoxide production in cultured rat aortic endothelial cells with possible involvement of the small GTP-binding (G) protein Rac1. The aldosterone levels showed a time-dependent (6-24 h) and dose-dependent (10(-8) to 10(-6) m) increase in superoxide gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 31 publications
6
91
0
2
Order By: Relevance
“…In addition, increased aldosterone concentrations may activate oxidative stress through an unregulated NADPH oxidase in the DOCA-salt model [35] . In agreement with previous report [25] we also observed that systolic and diastolic blood pressure was considerably increased in DOCA-salt hypertensive rats (group 3), which might be due to increased oxidative stress and decreased bioavailability of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased aldosterone concentrations may activate oxidative stress through an unregulated NADPH oxidase in the DOCA-salt model [35] . In agreement with previous report [25] we also observed that systolic and diastolic blood pressure was considerably increased in DOCA-salt hypertensive rats (group 3), which might be due to increased oxidative stress and decreased bioavailability of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it has also been demonstrated that aldosterone increased ACE gene expression in cardiovascular tissue via Rac1 dependent mechanisms. 22 Surprisingly, the beneficial effects of EPL on both atrial structural remodeling and the inducibility of AF were demonstrated in high blood pressure status. Of note, both increased ROS production assessed by HNE staining and activated Rac1 expression in DS+HS group were attenuated by EPL treatment only in LA, but not in LV.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Recently, some reports have revealed the relationship between MR activation and Rac1 activity. 21,22 However, little is known about the relationship between MR and Rac1 in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Rac1 binds to Cas, although Rac1 also binds to and is activated by RhoG and aldosterone in other settings [58,59]. We hypothesized that paxillin-Crk-Cas interaction might influence Rac1.…”
Section: Discussionmentioning
confidence: 99%